Fluorite Mineralization Related to the Dolomitization:an Equilibrium Study of the Proterozoic Stratabound Carbonate Macaia-Ijaci Basin, Lavras,Minas Gerais, Brazil - Sandra Cecília Miano; Fernando Roberto Mendes Pires; Carmen Lúcia Oliveira Mendes (Anuário do Instituto de Geociências, 2004)
Stratabound fluorite occurring as thin films in the concomitantlyderived dolomitic portions of the calcitic limestone of the ProterozoicCarandaí Formation in the Macaia-Ijaci Basin was supposedly formedby metasomatic reactions between the carbonate and HF- and Mg2+-rich brines, during metamorphism. Thirteen electron microprobeanalyses from the carbonate in a single petrographic thin section, allowedthe determination of the temperature of the carbonate formation in therange 180o-230oC, using the Mg-calcite solvus geothermometer. Fivekey mineral reactions in the system Mg-Ca-C-H-O-F plotted in diagramsin terms of either, CO2- and HF-fugacities or chemical potentials ofCO2 and HF yielding fluorite + dolomite from calcite + Mg2+, areproposed. Apparently the fluorite formation is related withdolomitization. Additional reaction involving fluorite was calculatedand inserted in the phase diagram, according to the existence of calcite-fluorite veinlets bordered by dolomite selvages, at the Casa de Pedraquarry.